Pengaruh Progressive Muscle Relaxation ( PMR) Terhadap Kualitas Tidur Ibu Hamil Trimester III di TPMB Yulia Kabupaten Malang - ANISSATUL VAUZAH; TUT RAYANI AKSOHINI WIJAYANTI; SULISTIYAH (Hang Tuah Medical Journal, 2026)
Due to the substantial hormonal and physiological changes that occur throughout pregnancy, it is a crucial time. These changes may occasionally result in sleep disruptions during the third trimester, such as trouble falling asleep and numerous awakenings during the night. The health of both the mother and the fetus can be negatively impacted by inadequate sleep in the later stages of pregnancy, which raises the risk of postpartum depression, prolonged labor, preeclampsia, and cesarean delivery. This study examined how third-trimester pregnant women at TPMB Yulia Tri Jayanti Turen, Malang Regency, slept better after using Progressive Muscle Relaxation (PMR). Twenty respondents were chosen by deliberate sampling for this pre-experimental study, which employed a one-group pretest-posttest design. The Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality both before and after the PMR intervention, which lasted for 10 to 15 minutes every day for two to four weeks.The data was examined using the Wilcoxon Signed Rank Test.According to the findings, all respondents (100%) had poor sleep quality prior to the intervention, while 45% had good sleep quality following it. After PMR, sleep quality significantly improved, according to statistical analysis (p = 0.003). By methodically tensing and releasing muscle groups, PMR lowers sympathetic nervous system activity, increases parasympathetic dominance, stabilizes heart rate and blood pressure, and encourages relaxation—all of which improve sleep. These results imply that PMR is a successful non-pharmacological treatment to enhance third-trimester pregnant women's quality of sleep.